Changing knowledge, attitudes and behaviours towards cytomegalovirus in pregnancy through film-based antenatal education: a feasibility randomised controlled trial of a digital educational intervention - Anna Calvert; Tushna Vandrevala; Robin Parsons; Victoria Barber; Alex Book; Gayle Book; David Carrington; Vanessa Greening; Paul Griffiths; Danielle Hake; Asma Khalil; Suzanne Luck; et al. (BMC, 2021)
Abstract Background Congenital cytomegalovirus (CMV) is the most common congenital infection globally, however information about CMV is not routinely included in antenatal education in the United Kingdom. This feasibility study aimed to gather the essential data needed to design and power a large randomised controlled trial (RCT) to investigate the efficacy of a digital intervention in reducing the risk of CMV acquisition in pregnancy. In order to do this, we carried out a single-centre RCT, which explored the knowledge, attitudes and risk reduction behaviours in women in the intervention and treatment as usual groups, pre- and post-intervention. Methods CMV seronegative women living with a child less than four years old, receiving antenatal care at a single UK tertiary centre, were randomised to the digital intervention or 'treatment as usual' groups. Participants completed questionnaires before the digital intervention and after and at 34 gestational weeks, and responses within groups and between groups were compared using tailored randomisation tests. CMV serology was tested in the first trimester and at the end of pregnancy. Results Of the 878 women screened, 865 samples were analysed with 43% (n = 372) being CMV seronegative and therefore eligible to take part in the RCT; of these, 103 (27.7%) women were enrolled and 87 (84%) of these completed the study. Most participants (n = 66; 64%) were unfamiliar with CMV at enrolment, however at 34 gestational weeks, women in the intervention group (n = 51) were more knowledgeable about CMV compared to the treatment as usual group (n = 52) and reported engaging in activities that may increase the risk of CMV transmission less frequently. The digital intervention was highly acceptable to pregnant women. Overall, four participants seroconverted over the course of the study: two from each study group. Conclusions A large multi-centre RCT investigating the efficacy of a CMV digital intervention is feasible in the United Kingdom; this study has generated essential data upon which to power such a study. This single-centre feasibility RCT demonstrates that a digital educational intervention is associated with increase in knowledge about CMV and can result in behaviour change which may reduce the risk of CMV acquisition in pregnancy. Trial registration Clinicaltrials.gov, NCT03511274 , Registered 27.04.18, http://www.Clinicaltrials.gov